Nerve stretch tests in patients with lumbar disc herniation - Aleksić, Vuk Milorad; Joković, Miloš (Medicinski podmladak, 2023)
A herniated disc occurs when an intervertebral disc displaces and compress a spinal nerve root. Nerve stretch tests or provocative tests have a great diagnostic value and are quite specific for the pathology of lumbar disc herniation. The nerve stretching tests that are most often used in order to prove or rule out compression on the spinal nerve root are: Lazarević’s test, Cram’s, Bragard’s, crossed-contralateral Lazarević’s test, inverted Lazarević’s or Fajerstein’s test, Bekhterev’s, Neri’s, Govers’ and Kernig’s tests, Lhermite’s sign, Dendy’s test, Milgram’s and Nafciger’s test, bowstring sign, Tandelenburg sign, Hoover’s simulation test, Menel’s, Genslen’s test and Patric-faber’s test. This article describes the techniques of performing all the mentioned tests, as well as their clinical significance.